2013
DOI: 10.1186/1471-2458-13-704
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a mobile application for smoking cessation in young people: study protocol for a clustered, randomized trial

Abstract: BackgroundTobacco consumption is the most preventable cause of morbidity-mortality in the world. One aspect of smoking cessation that merits in-depth study is the use of an application designed for smartphones (app), as a supportive element that could assist younger smokers in their efforts to quit. To assess the efficacy of an intervention that includes the assistance of a smoking cessation smartphone application targeted to young people aged 18 to 30 years who are motivated to stop smoking.Methods/designClus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 8 publications
0
39
0
1
Order By: Relevance
“…In our review of 92 HCI and health behavior change papers we found that there were very few studies designing technology to support smoking cessation, i.e. [4,16,25,28,29,30,34,35,41]. Within these, we did not find any designs created through participatory practices, such as focus groups and design workshops.…”
Section: Related Workmentioning
confidence: 82%
See 1 more Smart Citation
“…In our review of 92 HCI and health behavior change papers we found that there were very few studies designing technology to support smoking cessation, i.e. [4,16,25,28,29,30,34,35,41]. Within these, we did not find any designs created through participatory practices, such as focus groups and design workshops.…”
Section: Related Workmentioning
confidence: 82%
“…Ploderer et al [28,29,30] focused their research on understanding social support amongst peers to inform the design of a "Distract Me" app for mobile phones. Valdivieso-López et al [41] focused on providing "healthy games" in a mobile app for teenagers. Murnane and Counts [24] analyzed posts on Twitter to discover how people succeed in quitting using social media, and Zhang and Yang [44] studied Facebook posts to discover patterns of behavior that aligned with smokers' quitting stages.…”
Section: Related Workmentioning
confidence: 99%
“…As identified in the literature review, the menu remains the traditional medium of communication, along with digital screens, but this study shows that there was openness to technical solutions such as smartphone apps, which not only solve the problem of information overload but also increase engagement with the customer. The advantages of individualisation, transparency, accuracy and user engagement were cited, and reflect those identified in the literature (see Van Rijswijk and Frewer 2012;Bundasak and Chinnasarn 2013;Kalnikaite et al 2012;Valdivieso-López et al 2013). There were concerns about the initial outlay of energy needed in terms of building a database, but in the long term, a digital solution was seen as a time-saving approach to information provision and likely to provide enhanced customer satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Through utilising web or mobile application-based methods, data can be tailored to the user (Kalnikaite et al 2012) and can promote greater engagement through interactivity (Valdivieso-López et al 2013). The potential of such web-based solutions for influence is enabled by the rapidly growing numbers of smart phone users, with such technology estimated to be used by over a third of the world's population and have penetration rates of 68.4% in North America and 64.7% in Western Europe (Statista 2017).…”
Section: Literature Review: Health Consciousness and The Need For Infmentioning
confidence: 99%
“…This difference also adds to the variability in duration of measurements of smoking cessation outcome. Despite a limited number of studies met the selection criteria few study protocols were found to be published 39,58 . This review is expected to guide future research with improved methods, sample size, and evidence-based design consideration to measure effect size.…”
Section: Review Papermentioning
confidence: 99%